Managing invariance of place identity across gender for wine cultural tourism - Yen, Tsaifa (IJRDO - Journal of Business Management, 2019)
This study was aimed at investigating the invariance of place identity across gender in the context of wine cultural region at Yibin, China. Questionnaire survey was employed to collect the data. Applying the quota sampling technique in Yibin region, China,a total number of 276 usable samples were obtained, resulting in a response rate of 92%. The findings showed that the property of measurement weights and structural residuals across the gender was equivalent but the measurement residuals were not. The scales developed by previous studies achieved partial measurement invariance for wine culture tourism. Some suggestions were offered to the marketers and future studies.